Gambaran Tawakal Pada Mahasiswa Yang Memiliki Penyakit Kronis - Zulkifli, Munirah; Hairina, Yulia; Mubarak, Mubarak (Jurnal Al-Husna, 2020)
Chronic illness is a dangerous disease that cannot be underestimated or ignored because it can cause death at any time, but this is not an excuse for some students at UIN Antasari where they live and continue their studies well even though in their bodies there are diseases that can cause death, this is because they choose to trust God because with trust they can live their lives better. So from that researchers are interested in examining the description of the trust process in students who have chronic diseases at UIN Antasari Banjarmasin and factors that influence attitudes trust.  This research uses a qualitative approach. The subjects in this study were 3 students of UIN Antasari who had chronic diseases.  Data collection in this study was obtained using Anecdotal Record observation techniques, and semi-structured interviews.  After the data is collected, it is then analyzed with the stages of editing, coding, description and concluding data.  Based on the results of this study, there are several aspects that arise after making trust, such as the emergence of calm and peace, generate strength, Rida, and the emergence of hope. The factors that influence tawakal behavior are, first, the environmental factors which come from the surrounding environment such as family, friends and the community.  These two factors are experiences in which the fator is able to provide input for life values.